Si Vis Pacem, Para Bellum?: Perspektif Pacifisme Kristen - Widjaja, Paulus Sugeng (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2024)
AbstractWar after war has been fought on earth for centuries, without a single one succeeding in bringing true peace. However, there are still many people and state leaders, including church leaders, who believe in the truth of the proposition “Si vis pacem, para bellum”. This article shows that the proposition is problematic since it originates from the national security paradigm. This article emphasizes the need to understand peace positively and actively, as a comprehensive idea related to relations and interconnectedness between humans and between humans and the non-human natural environment. In this light, Christian pacifism calls for the church and Christians to abandon all forms of violence, including war, as they are not in accordance with Christian ethics. It seeks peace that is based on symbiocentric paradigm, which considers not primarily the security of oneself and one’s group exclusively, but the sustainable well-being of all life. Christian Pacifism also calls on everyone to abandon the safety net of moral certainty, for Christian Pacifism is not primarily a technical or methodological issue related to war; about which methods can be more effective in resolving conflicts. Christian pacifism is a matter of faith and repentance. Equipped with this belief, churches and Christians can embody the Pancadharma of Peace which contains the Christian virtues of hope, vulnerability, humility, patience, and empathy. AbstrakPerang demi perang telah terjadi di bumi selama berabad-abad lamanya, tanpa satu pun berhasil membawa perdamaian sejati. Namun demikian, masih banyak orang dan pemimpin negara, termasuk pemimpin gereja, yang meyakini kebenaran dalil “Si vis pacem, para bellum”. Tulisan ini menunjukkan bahwa dalil tersebut bermasalah karena bersumber dari paradigma national security. Tulisan ini menekankan perlunya  memahami perdamaian secara positif dan aktif, sebagai sebuah gagasan komprehensif terkait relasi antarmanusia dan antara manusia dan alam lingkungan non-manusia. Dalam terang itu, pacifisme Kristen memanggil gereja dan orang-orang Kristen untuk meninggalkan segala macam bentuk kekerasan, termasuk perang, karena tidak sesuai dengan etika Kristen. Pacifisme Kristen mencari upaya perdamaian yang dilandaskan pada paradigma symbiocentric yang memperhitungkan bukan terutama keamanan diri sendiri dan kelompok sendiri secara eksklusif, tetapi kesejahteraan seluruh kehidupan yang berkelanjutan. Pacifisme Kristen juga mengajak semua orang meninggalkan jaring pengaman kepastian moral, karena pacifisme Kristen bukan terutama masalah teknis atau metodologis terkait perang; tentang metode mana yang lebih efektif dalam penyelesaian konflik. Pacifisme Kristen adalah persoalan iman dan pertobatan. Berbekal keyakinan inilah gereja dan orang-orang Kristen bisa menghidupi dan membudayakan Pancadharma Perdamaian yang berisi kebajikan-kebajikan Kristiani, yaitu: pengharapan, kerentanan, kerendahan-hati, kesabaran, dan empati.